2018
DOI: 10.24106/kefdergi.428598
|View full text |Cite
|
Sign up to set email alerts
|

Suriyeli Öğrencilerin Okula Uyumları Hakkında Öğretmen Görüşleri

Abstract: Problem durumu: Bu çalışmanın amacı, eğitimlerine Türkiye'deki okullarda devam eden Suriyeli çocukların okula uyum süreçleri hakkında öğretmenlerin görüşlerinin alınmasıdır. Yöntem: Araştırmada nitel araştırma yöntem ve teknikleri kullanılmıştır. Araştırma verileri, yarı yapılandırılmış görüşmeler yoluyla toplanmış ve içerik analiziyle çözümlenmiştir. Bulgular: Araştırmanın bulgularına göre, Suriyeli öğrencilerin yaşadıkları en büyük problemin Türkçe bilmemeleri ve akranları ile uyum sorunu yaşamaları olduğu; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(9 citation statements)
references
References 9 publications
2
3
0
4
Order By: Relevance
“…The teachers stated that they were not informed about the refugee students and the institution had not been prepared for them. This result routes us to the findings of Kiremit et al (2018) and Kardes and Akman. ( 2018) that there are teacher competence and teacher adaptation problems.…”
Section: Discussionsupporting
confidence: 83%
“…The teachers stated that they were not informed about the refugee students and the institution had not been prepared for them. This result routes us to the findings of Kiremit et al (2018) and Kardes and Akman. ( 2018) that there are teacher competence and teacher adaptation problems.…”
Section: Discussionsupporting
confidence: 83%
“…Hence, education which is mostly related with communication is significantly affected from the language problem. Many studies in the literature (Cin, 2018;Erdem, 2017;Levent & Çayak, 2017;Kiremit et al, 2018;Mercan Uzun & Bütün, 2016;Sarıer, 2020;Sarıtaş et al, 2016;Tosun et al, 2018) one of the difficulties encountered in the refugee students studying in Turkey and perhaps seen as the most important of the language problem. In meta-synthesis study by Sarıer (2020), it was concluded that refugee students had communication problems due to language problem, could not express themselves, had difficulty learning language, and resisted learning.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these results, language problems (Başar, Akan, & Çiftçi, 2018;Kardeş & Akman, 2018;Kiremit, Akpınar, & Akcan, 2018;Şahin & Sümer, 2018;Tösten, Toprak, & Kayan, 2017), adaptation problems (Başar et al, 2018;Kardeş & Akman, 2018;Toker-Gökçe & Acar, 2018;Uzun & Bütün, 2016), teacher adaptation (Sağlam & Kanbur, 2017;Kiremit et al, 2018) and teacher competence (Kardeş & Akman, 2018;Şahin & Sümer, 2018) were found to be the key issues and problems put forward by the teachers. Some other minor problems were also revealed such as disruption (Kiremit et al, 2018), overcrowded classrooms (Tösten, et al, 2017), and lack of equipment (Şahin & Sümer, 2018). It was also found that people, in general, do not have negative attitudes toward Syrians (Çiftçi, 2018), and that teachers who have Syrian children in their classroom have better attitudes than those teachers who do not have any Syrian children in their classrooms (Sağlam & Kanbur, 2017).…”
Section: Studies Of Teacher Views On Refugees' Education In Turkeymentioning
confidence: 96%